Islamisasi di Jambi oleh Pangeran Wirokusumo (1860 - 1902) - Siregar, Isrina; Niswari, Vina Ayu; Sinurat, Junita Yosephine; Ramli, Supian; Agustiningsih, Nur (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2024)
The history of Prince Wiro Kusumo or Al-Habib Sayyid Idrus bin Hasal Aljufri left traces of Islamic heritage through the Olak Kemang Stone House in Sebrang City, to be precise, Olak Kemang Village, Jambi. It was there that Prince Wiro Kusumo and his colleagues preached to the public to spread Islam, whose development is still being felt today. This research is used to identify the role of Prince Wiro Kusumo in spreading Islam in Jambi and what was used as a medium of preaching at that time. This study employed a descriptive qualitative methodology. The study findings suggest that Prince Wiro's participation and services had a significant impact on the advancement of Islam, especially in Jambi Province itself, which is a history that must be known by the public, not only in Jambi Province but also abroad.